Statistical multiparameter sensitivity measures for transfer gain and phase functions - Cevdet, Acar (Wiley, 1979)
AbstractNew statistical multiparameter sensitivity measures are defined for the transfer, gain and phase functions. The integrands of these sensitivity measures include mean values as well as variances of element variations. It is shown that a very simple relationship exists between transfer, gain and phase measures even though element variations are large. General formulae are derived for small element variations, which would simplify evaluation of the measures. These formulae are helpful in the comparison of various low sensitivity networks.
Keywords: Transfer; Analytic circuit theory; Statistical Multiparameter Sensitivity Measures; Network; Phase Functions; Gain